Analysis Of Investment Feasibility To Additional Mushroom Cultivation Hotties In Kayu Embun MSMES In Main Sumatera - Yelita Anggiane Iskandar; Aviva Ilsanti Putri; May Putri Fadillah; Sindi Nasratul Huda; Sri Nuraini; Zahra Ashshabrina; Resista Vikaliana (Universitas 17 Agustus 1945 Surabaya, 2023)
Small and Medium Enterprise (SME) Kayu Embun located in North Sumatra Province is a business that focuses on agriculture of mushroom cultivation. Since starting the business, they have always been busy handling sales because the product's quality is known to be good, so high demand often occurs occasionally. Therefore, this SME plans to build a new cultivation hut to fulfill increasing customer demand. The purpose of this research is to determine the feasibility of investing in additional oyster mushroom huts in the SME Kayu Embun using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods. In NPV calculations, a value of IDR79,991,344 is obtained, where the acquisition value is more than 0. Calculations using the IRR method obtain a value of 292%, which is greater when compared to the value of the interest rate of 5.57% while using the PP method, we obtain a result of 0.35 years or 4.21 months which is < 4 years (the operational life of the mushroom hut) hence it can be concluded that the investment in adding oyster mushroom huts is feasible.